2019
DOI: 10.1111/exd.14048
|View full text |Cite
|
Sign up to set email alerts
|

Why is hair curly?—Deductions from the structure and the biomechanics of the mature hair shaft

Abstract: The final shape of a head hair is predetermined through a variety of factors during its formation in the follicle. These are genetic pathways, specific growth factors, cell differentiation and segregation, etc, with spatial as well as chronological dynamics. The cortex of hair consists of two major cell groups. These are characterized by parallel (para‐type) or roughly helical arrangements (ortho‐type) of the intermediate filaments (IF). There are also cell‐specific differences in the disulphide content, that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 87 publications
(257 reference statements)
3
31
0
Order By: Relevance
“…the effect of cross-sectional eccentricity on curvature). In this sample, we were able to show that eccentricity does not predict hair curvature, which is in line with the findings of other studies 8,13,21 . In fact, we explain this correlation as arising due to uncorrected population structure, which induces correlations between traits that are not necessarily genetically or physically linked.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…the effect of cross-sectional eccentricity on curvature). In this sample, we were able to show that eccentricity does not predict hair curvature, which is in line with the findings of other studies 8,13,21 . In fact, we explain this correlation as arising due to uncorrected population structure, which induces correlations between traits that are not necessarily genetically or physically linked.…”
Section: Discussionsupporting
confidence: 92%
“…West African) and the presence of round cross-sections in populations with straight hair (i.e. East Asian) has been interpreted as evidence that cross-sectional shape of hair dictates its curvature 8,9 . Whether these two traits are genetically and/or developmentally correlated is unknown because of population structure, which induces spurious correlations between traits 10 .…”
Section: Resultsmentioning
confidence: 99%
“…West African) and the presence of round cross-sections in populations with straight hair (i.e. East Asian) has been interpreted as evidence that cross-sectional shape of hair dictates its curvature 2 , although this has been refuted by others 12 , 13 , with some suggesting a synergistic link rather than a causal one 14 . Whether these two traits are genetically and/or developmentally correlated is unknown because of population structure, which induces spurious correlations between traits 15 .…”
Section: Resultsmentioning
confidence: 99%
“…Compared to cross-sectioning, longitudinal sectioning of hair makes it possible to analyze a broader cortex surface area, providing more information per analysis. This method of sectioning also circumvents the issue of analytical uncertainty related to the fact that the shape of cross-sections along the length of the hair can vary between circular, triangular, irregular, or flattened [102][103][104]. Studies have demonstrated that longitudinal sectioning of hair enables the identification of analyte accumulation patterns which may reveal whether compounds are contaminants or endogenous to the hair medulla [50,105].…”
Section: Longitudinal Sectioning Of Hair Strandsmentioning
confidence: 99%